Hysteresis and Damping Analysis of Tensegrity Structures through Nonlinear Finite Element Modeling - Kaan Yildiz (Havacılık ve Uzay Teknolojileri Dergisi)
Tensegrity structures, composed solely of axial load carrying elements, have been considered for space applications from various aspects. Resilient tensegrity-based robots, designed for the exploration of celestial bodies, are planned to be launched from spacecraft in orbit and require no additional landing mechanisms as the impact loads are absorbed by the robot itself. Recent modeling studies for tensegrity structures’ damping capabilities employ an analytical approach where the governing equations are derived for specific geometries and solved using iterative schemes. In contrast, this work proposes a finite element model employing an elastoplastic material model to evaluate the energy absorption capabilities of tensegrity structures. The proposed model assesses the damping capabilities of tensegrity structures through hysteresis curves under cyclic compression loads, with struts, compressioncarrying elements, exhibiting distinct nonlinear behavior during loading and unloading. Based on the developed model, a comparative analysis of cylindrical tensegrity structures with three and four struts is carried out. Prestress values and applied external loads are varied to carry out a comprehensive analysis.